2017
DOI: 10.12968/bjon.2017.26.15.882
|View full text |Cite
|
Sign up to set email alerts
|

A tool for assessing the quality of nursing handovers: a validation study

Abstract: The Handoff CEX-Italian scale is valid and reliable and it can be used to assess the quality of nurse handovers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…After eliminating those written prior to 2015, those not written in Spanish or English, and articles that did not deal with the handover of critical patients in an emergency setting, the results were narrowed to eight [24][25][26][27][28][29][30][31]. After exhaustive reading, five were excluded [25][26][27][28]30] as the handover did not take place in the study setting. Finally, three articles [24,29,31] were included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After eliminating those written prior to 2015, those not written in Spanish or English, and articles that did not deal with the handover of critical patients in an emergency setting, the results were narrowed to eight [24][25][26][27][28][29][30][31]. After exhaustive reading, five were excluded [25][26][27][28]30] as the handover did not take place in the study setting. Finally, three articles [24,29,31] were included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Most handover evaluation tools available in the literature assess transfers that occur in non-emergency settings, where the patient is not in a critical condition [25][26][27][28]30]. On the other hand, most of the instruments identified that do evaluate handover in urgent care and emergency settings do not validate their application in that field and are, therefore, not considered validated assessment tools [21,33,34].…”
Section: Discussionmentioning
confidence: 99%
“… Inclusion: nurses from the selected departments who have successfully completed the period of tutoring  Exclusion: nurses who provide delivery not in their own ward. The observations of the nursing handovers, before and after the implementation of the SBAR methodology, were carried out by specifically trained nursing evaluators using the Handoff Check tool validated in Italian language (13). process and the level of agreement between evaluator and observed.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Changing handover method is complicated and requires effective implementation strategies and training reinforcement (8,12). The literature suggests the use of standardized nursing delivery models such as the SBAR model (5,(7)(8)(9)13,14). In 2007 the Joint Commission International (JCI) and the World Health Organization (WHO) suggested the implementation of a structured communicative delivery approach using the SBAR (Situation, Background, Assessment, Recommendation) technique as a precise and versatile handover tool (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that handoff communication in practice among nurses is a task of great difficulty and importance (Kim et al, 2016;Ferrara et al, 2017). Mutual handoff communication enables nurses not only to share information about nursing courses and acquire important guidance in nursing the sick, but it also shares personal information, including doctors' medical treatments, treatment protocols, patients' physical mental nursing contents, patients' economic conditions, family and social relationships, and awareness of health problems (Abraham et al, 2016;Lee et al, 2016;Lim and Pajarillo, 2016).…”
Section: Introductionmentioning
confidence: 99%